1998
DOI: 10.1091/mbc.9.2.345
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Proteins Act as Negative Regulators of the Mitotic Inducer Cdc25 inXenopusEgg Extracts

Abstract: Cdc25, the dual-specificity phosphatase that dephosphorylates the Cdc2–cyclin B complex at mitosis, is highly regulated during the cell cycle. In Xenopus egg extracts, Cdc25 is associated with two isoforms of the 14-3-3 protein. Cdc25 is complexed primarily with 14-3-3ε and to a lesser extent with 14-3-3ζ. The association of these 14-3-3 proteins with Cdc25 varies dramatically during the cell cycle: binding is high during interphase but virtually absent at mitosis. Interaction with 14-3-3 is mediated by phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
217
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(227 citation statements)
references
References 49 publications
9
217
0
Order By: Relevance
“…Studies of the interaction between Cdc25B and 14-3-3 clearly demonstrated that the binding of 14-3-3 masks the NLS of Cdc25B, thereby causing nuclear exclusion of the protein without affecting its phosphatase activity. Similar results were obtained with Xenopus Cdc25 (Kumagai et al, 1998;Kumagai and Dunphy, 1999;Yang et al, 1999). In Xenopus oocytes, PKA phosphorylated Cdc25-S287, resulting in direct interaction between Cdc25 with 14-3-3 and sequestration of Cdc25 away from its substrate, MPF, which would leave MPF inactive.…”
Section: Discussionsupporting
confidence: 81%
“…Studies of the interaction between Cdc25B and 14-3-3 clearly demonstrated that the binding of 14-3-3 masks the NLS of Cdc25B, thereby causing nuclear exclusion of the protein without affecting its phosphatase activity. Similar results were obtained with Xenopus Cdc25 (Kumagai et al, 1998;Kumagai and Dunphy, 1999;Yang et al, 1999). In Xenopus oocytes, PKA phosphorylated Cdc25-S287, resulting in direct interaction between Cdc25 with 14-3-3 and sequestration of Cdc25 away from its substrate, MPF, which would leave MPF inactive.…”
Section: Discussionsupporting
confidence: 81%
“…Cdc25C S287A cannot be phosphorylated by Chk1 and induces checkpoint-arrested egg extracts to enter mitosis (Kumagai et al, 1998b). The S287A mutant efficiently suppresses the cell cycle arrest caused by geminin depletion in a dose-dependent manner, as determined by the size and appearance of the embryonic cells after the MBT ( Figure 5B, top, black rectangles).…”
Section: Bypassing Chk1 Pathway Suppresses G2 Arrest Caused By Geminimentioning
confidence: 98%
“…Injection of the highest concentration of wild-type Cdc25C RNA partially suppresses the cell cycle arrest ( Figure 5B, top, gray rectangles) and partially reverses the phosphorylation of Cdc2 on tyrosine-15 (bottom, lane 7). Because phosphorylation of S287 does not inhibit phosphatase activity (Kumagai et al, 1998b), wild-type Cdc25C would be able to overcome the arrest once sufficient quantities were available to saturate the amount of 14-3-3 in the cytoplasm. Immunoblots showed that comparable amounts of the Cdc25C WT and S287A proteins were expressed at each RNA concentration (our unpublished data).…”
Section: Bypassing Chk1 Pathway Suppresses G2 Arrest Caused By Geminimentioning
confidence: 99%
“…The 14-3-3 proteins bind to phosphorylated Ser-216 of Cdc25C and induce Cdc25C export from the nucleus during interphase in response to DNA damage, 7,8 but they have no apparent effect on Cdc25C phosphatase activity. 9,10 In addition, hyperphosphorylation of Cdc25C correlates to its enhanced phosphatase activity. 11 Most studies with Cdc25C have focused on its role in mitotic progression.…”
mentioning
confidence: 99%